Impacts of elevated CO2 on exogenous Bacillus thuringiensis toxins and transgene expression in transgenic rice under different levels of nitrogen. Issue 1 (December 2017) - Jiang, Shoulin; Lu, Yongqing; Dai, Yang; Qian, Lei; Muhammad, Adnan; Li, Teng; Wan, Guijun; Parajulee, Megha; Chen, Fajun
Abstract Recent studies have highlighted great challenges of transgene silencing for transgenic plants facing climate change. In order to understand the impacts of elevated CO2 on exogenousBacillus thuringiensis (Bt ) toxins and transgene expression in transgenic rice under different levels of N-fertilizer supply, we investigated the biomass, exogenousBt toxins, Bt -transgene expression and methylation status inBt rice exposed to two levels of CO2 concentrations and nitrogen (N) supply (1/8, 1/4, 1/2, 1 and 2 N). It is elucidated that the increased levels of global atmospheric CO2 concentration will trigger up-regulation ofBt toxin expression in transgenic rice, especially with appropriate increase of N fertilizer supply, while, to some extent, the exogenousBt -transgene expression is reduced at sub-N levels (1/4 and 1/2N), even though the total protein of plant tissues is reduced and the plant growth is restricted. The unpredictable and stochastic occurrence of transgene silencing and epigenetic alternations remains unresolved for most transgenic plants. It is expected that N fertilization supply may promote the expression of transgenic Bt toxin in transgenic Bt rice, particularly under elevated CO2 .